Konsep Nusyuz dalam Mazhab Syafi’i Perspektif Keadilan Gender - Meitayani, Dwi (Al-Manahij: Jurnal Kajian Hukum Islam, 2010)
The idea of nusyuz in Syafi’i mazhab is interesting because it supports gender equity and can be seen from two perspectives, men and women.